'Acknowledge me as a capable person': How people with mental ill health describe their experiences with general emergency care staff – A qualitative interview study. (30th June 2021) - Derblom, Katharina; Molin, Jenny; Gabrielsson, Sebastian; Lindgren, Britt‐Marie
Abstract: People with mental ill health attend general emergency care more often than others for physical and psychiatric care needs. Staff in general emergency care report they lack knowledge and strategies to meet with and care for people with mental ill health. This study aimed to describe how people with mental ill health experience encounters with staff in general emergency care. We conducted individual semi‐structured interviews with 11 people with mental ill health about their experiences in general emergency care and subjected the interview data to qualitative content analysis. Our results show the importance to people with mental ill health of being acknowledged as capable persons, and how this relates to their experiences of being recognized, ignored, or dismissed by staff in general emergency care. Even small, ordinary aspects of staff/patient interactions can have major impacts on a person's recovery and well‐being. The study is reported according to the consolidated criteria for reporting qualitative research (COREQ) guidelines.